The environmental factors affecting service satisfaction of community hospital - Tanut Waroonkun (2018)
© 2018, University of Malaya. All rights reserved. Community Hospital in Thailand is a small-size hospital and available at a ‘local level. Established by the Thai government some thirty years ago, the hospitals now find their facilities are unable to cope with increasing numbers of patients due to population growth. The re-furbishment of the old buildings in the hospital was needed in order to respond to these changes. Past extensions to the hospitals have focused more on form and function of the built environment rather than “needs” of the users (patients/family). However, research has shown that there are multiple aspects that affect a positive user experience in a hospital. This is especially true for the environmental aspect, which helps patients feel more comfortable and relaxed both mentally and physically when using community hospital services. There is a need therefore, to establish which of the environmental factors are important to a positive user experience. In this study, factors related to the built environment and their effect on the user experience were broadly categorized as Ambient Features, Architectural Features, Interior Design Features and Outdoor Environment Features. Each of these consisted of further sub-categories of importance to the user. Twenty users of Sara Phi Community Hospital were interviewed to determine what was important to them as users of the hospital. This hospital was chosen for convenience. The AHP model was used to establish a rank order of those factors considered important in determining user satisfaction. In-depth interview and questionnaires provided data for final analysis. The study found that Ambient Features had the highest impact score (0.343) followed by Architectural Features (0.260), Interior Design Features (0.224) and Outdoor Environment Features (0.173). The secondary factors that make up the main factors were ranked according to their weighted contribution to overall satisfaction. The paper discusses these factors with support for the respective rank. Suggestions are made for future development of this strategy of investigation.